India’s Edible Oil Woes productivity and policy imperatives - Suresh, A.; Jha, Girish Kumar (Indian Farming, 2016)
Vegetable oils constitute the single largest food commodity groupimported to India. The major strategies for improving the productivity of oilseeds could include (i) expansion of area under the oilseed crops, (ii) strategies to enhance the productivity and (iii) imparting resilience to the crop to face the climate risks and challenges.